Futatsu No Bunka: Penciptaan Ready To Wear Deluxe Bergaya Kimono Kurotomesode Dengan Aplikasi Motif Wayang Rama Shinta - Fatma Delaneirabudy, Giazkha; Budiono, Nadia Rachmaya Ningrum; Fitra, Annisa (Jurusan Seni Rupa ISBI Bandung, 2024)
This research discusses the development of new clothing by combining two different cultural icons, namely the Kurotomesode Kimono from Japan and the Rama Shinta Wayang from Indonesia. This design is based on the desire to create a fashion work that combines the essence of the two cultures, namely a ready to wear deluxe work with a kurotomesode kimono style and the application of the Wayang Rama Shinta motif, this also shows a unique combination of traditional Japanese beauty and the richness of Indonesian culture. The method used is exploration, design, and realization, with a focus on embroidery techniques on the Wayang Rama Shinta motif. The result is six fashion works that will be exhibited at the 2024 Jogja Fashion Parade.